Conjugated microporous polytriphenylamine as a high-performance anion-capture electrode for hybrid capacitive deionization with ultrahigh areal adsorption capacity - Kong, Weiqing; Lu, Xiaoyuan; Ge, Xu; Zhang, Qingao; Jin, Xiaoyu; Zhang, Meng; Feng, Yuanyuan (Journal of materials chemistry. A, Materials for energy and sustainability, 2024)
Conducting polymers with good electron conductivity and rich redox functional groups have attracted considerable attention as anode materials for capacitive deionization (CDI) towards overcoming global freshwater scarcity. However, because of their intrinsically poor porosity and severe particle aggregation nature, conducting polymers used for CDI desalination suffer the disadvantage of low specific surface areas (<50 m 2 g −1 ), sluggish ion diffusion kinetics, limited desalination capacities, and low mass loadings (∼1 mg cm −2 ) on electrodes. Herein, we synthesized amino group-rich conjugated microporous polytriphenylamine (m-PTPA) and for the first time demonstrated its great potential as a high-performance anion-capture electrode material in CDI applications. m-PTPA possesses reversible redox properties, predominant microporous characteristics (<2 nm diameter), and ultrahigh specific surface area (506 m 2 g −1 ), which ensured fast ion transport within the interconnected porous network and maximized the exposure of electrochemical active sites to saline solutions. Owing to these novel features, an m-PTPA-based CDI device, with m-PTPA as the anode at a high mass loading of 8.7 mg cm −2 and activated carbon as the cathode, exhibited high gravimetric/areal/volumetric-normalized salt adsorption capacities (47.21 mg g −1 , 0.41 mg cm −2 , and 10.92 mg cm −3 , respectively), fast adsorption rate (2.83 mg g −1 min −1 ), low energy consumption, and excellent cycling stability. Besides, we evaluated the competitive adsorption of some common anions existing in water and probed the mechanism for Cl − adsorption on m-PTPA. We believe that this work paves a new way for the use of conjugated microporous polymers as a new type of CDI electrode material. We report conjugated microporous polytriphenylamine as a high-performance anion-capture electrode for capacitive deionization (CDI), thus opening a new pathway for the rational design of advanced polymer-based anodes in CDI and beyond.